Implementasi Konsep Masyarakat Ekonomi Syariah Berbasis Organisasi Keagamaan - Afandi, Irfan; Mahmud, M. Amir; Aziz, Abdul; Rahman, Kholilur (Universitas Nurul Jadid, 2025)
The urgency of this Community Service lies in the implementation efforts of synergy between religious communities and the community economy towards shared prosperity. The community service is located in Sidorejo village; has a population of 7,804 people and 6936 of them are Muslims who are active in the Nahdlatul Ulama (NU) organization. Therefore, Sidorejo Village is known as a 'NU village' which has great potential in implementing the concept of a sharia economic society. Community service with the theme of Assistance in the Implementation of the Concept of a Sharia Economic Society (MES) Based on Religious Organizations in Sidorejo Village, Purwoharjo, Banyuwangi uses the Asset-Based Community Development (ABCD) approach which goes through five main stages: Discovery, Dream, Design, Define, and Destiny. The results of the community service that has been carried out are an increase in understanding and implementation of sharia economics which is concentrated on a). socialization of the dangers of usury in the NU community, this activity is carried out in 9 (nine) Yasin Congregations, b). How to make a contract in goat business according to sharia by creating a sharia livestock community; and c. how to utilize the potential of Islamic social finance such as zakat, infaq and shodaqoh (ZIS). Maximizing the potential of ZIS is by creating opportunities for sources of ZIS income; and creating a 'BPJS NU' card or a free health insurance system for dhu'afaa in the form of a health card; in addition to regular dhu'afaa and orphan assistance. The model for implementing a sharia economic society (MES) based on religious communities is locally called the Ranting Ekonomi Syariah (REKSYA) NU.